Analysis of Needs for Biology E-Module Based on Local Wisdom North Maluku, Indonesia - Haerullah, Ade; Hasan, Said; Sahil, Jailan (International Journal of Social Service and Research, 2023)
The content of learning material is packed with the local wisdom of an area which is taught using examples related to local wisdom, so students will easily understand the knowledge being taught and can relate the knowledge obtained to real situations that are close to students' daily lives. This study aims to analyze students' needs for interactive digital modules based on North Maluku local wisdom. This type of research is development research (R&D) using the ADDIE model. The data obtained used interviews with biology teachers and also used questionnaires via Google form to 88 students spread across several high schools in Ternate City, North Maluku, Indonesia. As for the student needs analysis questionnaire consisting of seven indicators, all research data obtained was analyzed descriptively qualitatively. The results showed that: 1) The content of biology material taught in high school has not been integrated with local wisdom, 2) the learning resources used are textbooks, worksheets, e-books, videos, and internet media, 3) as many as 64.2 % of students said they had never used e-modules, 73.5% of students did not understand local wisdom in North Maluku, and as many as 75.1% of students stated that there was a need for interactive modules to support biology learning, thus it can be concluded that e-modules need to be developed biology based on the local wisdom of Ternate, North Maluku as a supporting learning resource in learning biology in high school.